Analysis Of Factors Influencing Cervical Cancer Screening Behavior In Women Of Reproductive Age (WUS) - Wulansari; Makhrajani Majid; Fitriani Umar; Arfianty Arfianty; Henni Kumaladewi Hengky (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2022)
Background: Cervical cancer is the fourth most common cancer affecting and killing women and is more common in developing countries than in developed countries. Objective: To determine the impact of knowledge, education, attitudes, and family support on cervical cancer screening behavior among women of childbearing potential (WUS) at the Lapadde Health Center in Parepare City. Methods: This type of study is analytical with a cross-sectional design. The sample for this study was women of childbearing age who were married up to 98 using a targeted sampling technique. A questionnaire was used as a means. Data analysis used Fisher's exact test with p-value < 0.05. Results: The results showed that WUS still lacked knowledge and information. There is testing anxiety and lack of family support, resulting in lack of screening coverage. Conclusions: The study concluded that knowledge level (p=0.040), attitudes (0.036), and family support (p=0.012) had an effect on cervical cancer screening behavior, whereas education had no effect (p=0.674). Early detection behavior for cervical cancer. WUS recommends that he take the exam at least once every three years Keywords: Early detection of cervical cancer. HPV DNA; cervical cancer; pap smear; IVA test.